2013
DOI: 10.12669/pjms.294.3450
|View full text |Cite
|
Sign up to set email alerts
|

Knowledge and psychomotor skills of nursing students in North Cyprus in the area of cardiopulmonary resuscitation

Abstract: Objective : The aim of the study was to determine the cardiopulmonary resuscitation (CPR) knowledge and skill levels of nursing students in North Cyprus. Methods : The study design was quasi-experimental and longitudinal. A questionnaire was applied to the students before the CPR lecture. Then the students were informed about adult CPR by the researchers and all of the students practiced CPR on a Resusci-Anne manikin. One and six months after this training the same questionnaire and skills checklist of CPR wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
2
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 11 publications
1
27
2
2
Order By: Relevance
“…Dal and Sarpkaya (2013) evaluated the level of knowledge and skills of nursing students (n = 83) on cardiopulmonary resuscitation at the end of a 6-week training course conducted on a manikin in the laboratory setting. At the end of the study, it was concluded that this training provided an increase in the knowledge and skills of students on cardiopulmonary resuscitation.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dal and Sarpkaya (2013) evaluated the level of knowledge and skills of nursing students (n = 83) on cardiopulmonary resuscitation at the end of a 6-week training course conducted on a manikin in the laboratory setting. At the end of the study, it was concluded that this training provided an increase in the knowledge and skills of students on cardiopulmonary resuscitation.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, timely, clear, and concrete feedback must be provided to students in a clinical setting, as this will contribute to improvements in their skills. Within this context, it is necessary to reinforce psychomotor skills in nursing training through repeated practical training (Dal and Sarpkaya, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…It should be carried out with great urgency to avoid permanent brain damage or even death that would result if the victim stays from 4 to 6 minutes without oxygen (2) . According to the World Health Organization (WHO) in 2008, 17 million people (48% of all deaths) died due to cardiovascular diseases, and mainly because of cardiac arrest (3) . It has been documented that 33% to 40% of cardiac arrests in developed countries occur in the hospital setting, and of the arrests that occur in the hospital setting more than 60% are first recognized by nurses (WHO, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…In another study, the mean performance score of nursing students was increased one month after the intervention, but it was reduced after six months (30). A study suggested that levels of skill were reduced over time.…”
Section: Discussionmentioning
confidence: 97%
“…The level of knowledge and performance in both groups was reduced three months after the intervention, but in the intervention group, they were still higher than that of the control group; it was not significant regarding knowledge, however. Nurses may forget something after a certain period and ensuring knowledge retention is essential for proper implementation of CPR (30). A lack of repeating education on CPR as a practice-based skill can reduce students' skills over time (31).…”
Section: Discussionmentioning
confidence: 99%